PELATIHAN APLIKASI E-TAXAKTI PEMENUHAN KEWAJIBAN PERPAJAKAN WAJIB PAJAK ORANG PRIBADI - Rubiatto Biettant; Sisca Damayanti; Licke Bieattant; Khairul Syawaludin (JURNAL PENGABDIAN MANDIRI, 2026)
The Indonesian tax system adopts a self-assessment mechanism that requires taxpayers to calculate, deposit, and report their tax liabilities independently in accordance with applicable regulations. To support the effectiveness of this system, the Directorate General of Taxes continues to modernize tax administration through the use of information technology, including e-registration, e-filing, e-billing, e-invoicing, and e-forms. The implementation of e-forms aims to facilitate reporting and increase taxpayer compliance, particularly in the submission of Annual Tax Returns. However, there are still obstacles in the form of limited access to learning and applicable simulation tools, especially for teachers as agents of tax education. Teachers' limited technical competence in calculating and reporting Personal Income Tax (PIT) due to the lack of practical training and the unavailability of an official dummy system as a learning medium. Therefore, this Community Service Activity (CSA) aims to improve teachers' understanding and skills in calculating and reporting Annual Personal Income Tax accurately and precisely. The activity methods included counseling, practical training, mentoring, and interactive discussions with the support of learning modules and the e-taxakti dummy application, which resembles the electronic tax reporting system. The results of the activity showed an increase in the participants' ability to calculate Personal Income Tax and fill out the Annual Tax Return Form 1770 S